Role of VEGF receptors in normal and psoriatic human keratinocytes: evidence from irradiation with different UV sources. - Jian-Wei Zhu; Xian-Jie Wu; Zhong-Fa Lu; Dan Luo; Sui-Qing Cai; Min Zheng (PLoS ONE, 2013)
Vascular endothelial growth factor (VEGF) promotes angiogenesis and plays important roles both in physiological and pathological conditions. VEGF receptors (VEGFRs) are high-affinity receptors for VEGF and are originally considered specific to endothelial cells. We previously reported that VEGFRs were also constitutively expressed in normal human keratinocytes and overexpressed in psoriatic epidermis. In addition, UVB can activate VEGFRs in normal keratinocytes, and the activated VEGFR-2 signaling is involved in the pro-survival mechanism. Here, we show that VEGFRs were also upregulated and activated by UVA in normal human keratinocytes via PKC, and interestingly, both the activated VEGFR-1 and VEGFR-2 protected against UVA-induced cell death. As VEGFRs were over-expressed in psoriatic epidermis, we further investigated whether narrowband UVB (NB-UVB) phototherapy or topical halomethasone monohydrate 0.05% cream could affect their expression. Surprisingly, the over-expressed VEGFRs in psoriatic epidermis were significantly attenuated by both treatments. During NB-UVB therapy, VEGFRs declined first in the basal, and then gradually in the upper psoriatic epidermis. VEGFRs were activated in psoriatic epidermis, their activation was enhanced by NB-UVB, but turned undetectable after whole therapy. This process was quite different from that by halomethasone, in which VEGFRs and phospho-VEGFRs decreased in a gradual, homogeneous manner. Our findings further suggest that UV-induced activation of VEGFRs serves as a pro-survival signal for keratinocytes. In addition, VEGFRs may be involved in the pathological process of psoriasis, and UV phototherapy is effective for psoriasis by directly modulating the expression of VEGFRs.